The Monotonicity of the Linear Complementarity Problem (Journal of Nonlinear Modeling and Analysis, 2024)
The monotonicity of the linear complementarity problem (LCP) isdiscussed in this paper. Both the monotone property about the single elementof the solution and the monotone property of the whole solution are presented.In order to illustrate the results, some corresponding numerical experimentsare provided.
Keywords: Linear complementarity problem; Solution; Monotonicity.